A Critical Cultural Wealth Model of First-Generation and Economically Marginalized College Students' Academic and Career Development. (February 2020) - Garriott, Patton O.
First-generation and economically marginalized (FGEM) college students are attending higher education institutions with increasing regularity. The unique experiences of these students call for career frameworks that capture their specific strengths and challenges. This article outlines a new model from which to conceptualize FGEM college students' academic and career development with a focus on structural, environmental, and intrapersonal factors previously shown to predict their academic and career success. Social–emotional crossroads and career self-authorship are positioned as central constructs in the model and proposed as critical pathways to FGEM students' academic and career development. Cultural wealth is offered as a form of capital that may promote FGEM students' academic and career success. Implications for future research, practice, and policy with FGEM students are described.